Oil and grease removal from wastewaters: Sorption treatment as an alternative to state-of-the-art technologies. A critical review - Ariana Pintor (2016)
Oil and grease (O&G) is a class of pollutants with very low affinity to water. Their removal from wastewaters is often challenging and involves the combination of different treatment technologies, according to the specifications for the treated water and the O&G substances involved. O&G can be classified according to its type and source and this influences the choice of the treatment process. This paper presents a review of the state-of-the-art technology on O&G removal. Treatment usually involves several steps, including primary, secondary and tertiary treatment. Gravity separators accomplish removal of free oil as a primary treatment. Secondary treatments include chemical, electrical and physical methods which target emulsified oil, such as, coagulation/flocculation, dissolved air flotation, electro-coagulation/flotation, and membrane separation. Tighter membranes and advanced oxidation processes can refine treatment in a tertiary step. Many of these treatments present, however, disadvantages such as production of hazardous sludge or high energy requirements. In this context, sorption as a secondary treatment is gaining focus in the literature, especially using natural organic sorbents. These present the advantages of lower cost and biodegradability, and may enable the recovery or recycling of sorbed O&G. Additionally, some of them may be reused up to a limited number of working cycles. Several kinds of sorbents and mechanisms for oil sorption and recovery are reviewed in this article. (C) 2016 Published by Elsevier B.V.